2018
DOI: 10.3390/sports7010007
|View full text |Cite
|
Sign up to set email alerts
|

Different Pathways Leading up to the Same Futsal Competition: Individual and Inter-Team Variability in Loading Patterns and Preseason Training Adaptations

Abstract: During the preseason, futsal players deal with large internal load, which may result in a reduction in physical performance. The aims of this study were to compare the session rating of perceived exertion training load (s-RPE TL) during the preseason between two teams; and to analyze the changes on the delayed-onset muscle soreness (DOMS), aerobic- and speed-power characteristics in players accumulating different s-RPE TL (Low (LTL) vs. High (HTL)). Twenty-eight players (Team A, n = 15; Team B, n = 13) were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 32 publications
(74 reference statements)
2
24
0
2
Order By: Relevance
“…The training contents showed a logical distribution in accordance with periodisation principles [2,8,19], where the conditional contents were more prominent in pre-season than in the other mesocycles. During the pre-season, Teixeira et al [8] reported 50% of the time focused on technical-tactical contents, giving them more importance than in our study, and reporting double the time on power and strength. Conversely, technical-tactical tasks had more weight during the in-season mesocycles, similar to other studies, reaching over 60%-70% of training volume [11] or even up to 90% [20].…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…The training contents showed a logical distribution in accordance with periodisation principles [2,8,19], where the conditional contents were more prominent in pre-season than in the other mesocycles. During the pre-season, Teixeira et al [8] reported 50% of the time focused on technical-tactical contents, giving them more importance than in our study, and reporting double the time on power and strength. Conversely, technical-tactical tasks had more weight during the in-season mesocycles, similar to other studies, reaching over 60%-70% of training volume [11] or even up to 90% [20].…”
Section: Discussionmentioning
confidence: 62%
“…Strength training was one of the most important contents during the pre-season, with the sessions being reduced in volume during the subsequent mesocycles, as reported by previous authors [11,20]. However, as said above, other studies with professional male futsal players reported much more time dedicated to this capability during the pre-season [8], which could indicate the need to increase the volume of strength training in female futsal teams due to its relevance of sport performance. This shows some differences in contents distribution according to sex, with more relevance of strength training in men.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations